Mã hóa mạng trong hệ thống mạng hợp tác chuyển tiếp (Network Coding on Cooperative Relay Netwoks) - Lâm, Sinh Công (Đại học Quốc gia Hà Nội, 2016)
In communication, Cooperative Diversity Relaying refers to devices com-municating with one another with the help of relays in order to increase the performance of the network. However, in one timeslot, the relay only trans-mits the signal of one source. Therefore, Network Coding is introduced to improve the throughput of the network. Combining Cooperative Relay Net-work and Network Coding should be studied toachieve signi cant bene ts and overcome some weakness. In this thesis, we consider the eect of Net- work Coding on Cooperative Relay Network. We propose to use Selection Decode-and-Forward instead of Traditional Decode-and-Forward protocol at the relay. We also use the instantaneous channel gains to calculate the outage probability of the proposal system model. The rest of the thesis is organized as follows. In Chapter II, the system model of a multiple-relay etwork is described. The outage probability is calculated in Chapter III. Finally, the conclusions and the future works are drawn in Section IV.